Harmonization of Electricity Construction Claim Prevention Mechanisms: Integration of Pre-Construction Documents, FIDIC Standards, and Standing Dispute Boards - Junaedi, Junaedi; Sebastian, Reza Rafly; Rahmiko, Eko; Yanuar, Riko; Hardjomuljadi, Sarwono; Sami’an, S. (CV. Social Politic Genius (SIGn), 2025)
Construction disputes in national strategic electricity projects often hinder cost and time efficiency. This problem is fundamentally rooted in pre-construction document uncertainty and the regulatory gap between national contracts and international standards. This research aims to analyze the juridical implications of incomplete Employer’s Requirements documents on claim validity. It also evaluates gaps in notification mechanisms and differences in work between SOE contract standards and the FIDIC Silver Book, and constructs a dispute-prevention harmonization model. The research method used is normative legal research, with statutory, comparative, and case approaches, applied to the Asahan 3 HEPP project. The results show that disputes in the execution phase are residues of errors in concept design in the pre-construction phase. This condition creates information asymmetry and injures the principle of good faith. Comparative analysis reveals significant gaps in variation and substantiation procedures. Bureaucratic rigidity in national contracts due to the disharmony between Law Number 2 of 2017 and the state finance regime hinders rapid resolution compared to the FIDIC early warning system. However, empirical evidence shows that SDB activation can effectively mitigate conflict escalation. The research concludes that the ideal harmonization model must transform the paradigm from dispute resolution to dispute prevention. This is achieved by integrating SDB institutionalization with the validity of BIM digital data as indisputable primary evidence. This step is necessary to guarantee legal certainty and the sustainability of national strategic projects.